Pembelajaran Bermuatan HOTS (Higher Order Thinking Skill) di Jurusan Tadris Bahasa Indonesia - Indrya Mulyaningsih; Itaristanti Itaristanti (Jurusan Tadris Bahasa Indonesia, 2018)
This qualitative descriptive study aims to describe learning with HOTS content for students as prospective teachers. The study population consisted of all lecturers and students of the Indonesian Department of Social Sciences FITK IAIN Syekh Nurjati Cirebon. The research sample included: 4 lecturers and 117 students. Data was collected through questionnaires, interviews, and observations. The results of the study indicate that learning in the Indonesian Department of Social Sciences has been loaded with HOTS. However, there are still characteristic institutions and faculties that have not been charged with HOTS. Therefore, it should be necessary to improve the lecturers who are characteristic of the Institute and Faculty. Learning courses that characterize the Department have carried out HOTS activities. The course characterization bills are not only in the form of papers, but products. These products can be enjoyed by the general public, both in the form of performances and books.Penelitian deskriptif kualitatif ini bertujuan untuk mendeskripsikan pembelajaran bermuatan HOTS bagi mahasiswa sebagai calon guru. Populasi penelitian terdiri atas semua dosen dan mahasiswa Jurusan Tadris Bahasa Indonesia FITK IAIN Syekh Nurjati Cirebon. Adapun sampel penelitian, meliputi: 4 dosen dan 117 mahasiswa. Data dikumpulkan melalui angket, wawancara, dan pengamatan. Adapun hasil penelitian menunjukkan bahwa pembelajaran di Jurusan Tadris Bahasa Indonesia sudah bermuatan HOTS. Namun demikian, masih terdapat mata kuliah penciri Institut dan Fakultas yang belum bermuatan HOTS. Oleh karena itu, hendaknya perlu ada perbaikan bagi para dosen pengampu mata kuliah penciri Institut dan Fakultas. Pembelajaran mata kuliah penciri Jurusan sudah melakukan aktivitas HOTS. Tagihan mata kuliah penciri Jurusan tidak hanya berupa makalah, tetapi produk. Produk tersebut dapat dinikmati oleh masyarakat umum, baik berupa pementasan maupun buku.